An annotated checklist of the praying mantises (Mantodea) of Borneo, including the results of the 2008 scientific expedition to Lanjak Entimau Wildlife Sanctuary, Sarawak - Schwarz, Christian J.; Konopik, Oliver (Zootaxa, 2014)
We present the first checklist of praying mantids (Mantodea) of Borneo, with special reference to the specimens collected during the Scientific Expedition to Lanjak Entimau Wildlife Sanctuary 2008. With 118 confirmed species in 56 genera (including subgenera), Borneo is the island with the highest mantodean diversity known to date. In Lanjak Entimau 38 specimens representing 17 genera and 18 species were collected around the station lights and in surrounding secondary and primary forest. A new synonymy in the genus Deroplatys is established. The observed diversity patterns among Bornean mantids are discussed with reference to the biogeographic history of the Sunda Shelf since the Miocene.